2010
DOI: 10.1371/journal.pcbi.1000670
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model of Dopamine- and Calcium-Dependent Striatal Synaptic Plasticity

Abstract: Corticostriatal synapse plasticity of medium spiny neurons is regulated by glutamate input from the cortex and dopamine input from the substantia nigra. While cortical stimulation alone results in long-term depression (LTD), the combination with dopamine switches LTD to long-term potentiation (LTP), which is known as dopamine-dependent plasticity. LTP is also induced by cortical stimulation in magnesium-free solution, which leads to massive calcium influx through NMDA-type receptors and is regarded as calcium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 105 publications
(164 reference statements)
4
97
2
2
Order By: Relevance
“…Nakano et al specifically explored the contribution of dopamine signaling to AMPAR trafficking in striatal neurons (18). Although the Nakano computational model contained the core signaling steps of dopamine-mediated AMPAR insertion, it did not agree with our experimental data.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…Nakano et al specifically explored the contribution of dopamine signaling to AMPAR trafficking in striatal neurons (18). Although the Nakano computational model contained the core signaling steps of dopamine-mediated AMPAR insertion, it did not agree with our experimental data.…”
Section: Resultscontrasting
confidence: 63%
“…Previous models of dopamine signaling have highlighted the importance of a positive feedback loop between PKA, PP1, and DARPP-32/I1 on AMPAR trafficking (18,20). In this study, we propose a unique regulatory motif involving ERK-mediated regulation of PDE4, resulting in an increase in the activation of PKA and its downstream effectors.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Mathematically speaking, the BCM theory is expressed as: . It is further to be noted that synaptic plasticity is known to be related to the ratio of NMDA/AMPA receptor expressions at the postsynaptic neurons [10] and an increased proportion of NR2B-containing NMDA receptors at silent synapses in the nucleus accumbens [11].…”
Section: Bienenstock-cooper-munro Theory Of Synaptic Plasticitymentioning
confidence: 99%
“…There is a growing body of evidence that Mg plays an important role in synaptic plasticity and is involved in long--term potentiation (LTP) and long--term depression (LTD) of synaptic transmission . LTP is induced by cortical stimulation in Mg--free solutions and it is associated with massive calcium influx through NMDA--type receptors (Nakano et al, 2010). Diamond et al, (2007) suggested that complex interactions between LTP and LTD processes in the hippocampus contribute to the storage of emotional memories and stress--induced amnesia.…”
Section: Neurological Function Of Magnesiummentioning
confidence: 99%